PROGRAM FISIOTERAPI PADA AKUT SPINAL CORD INJURY ASIA C INCOMPLETE: SEBUAH STUDI KASUS - Dinik Ayundya Marli; Farid Rahman (Journal of Health Science and Physiotherapy, 2021)
A spinal cord injury or spinal cord injury is nerve damage to the nerves along the spine or in the spinal cord. With the highest cause of trauma due to traffic accidents 38%, in Indonesia the percentage of deaths due to spinal trauma is 24% and permanent disability is 45%. When spinal cord damage, it will cause complete or incomplete paralysis which can affect a person's functional activities. When this dysfunction occurs if not treated immediately with surgery it will cause secondary problems, therefore physiotherapy treatment in the acute phase has the main goal to prevent secondary problems that occur such as contractures, muscle atrophy, deep vein thrombosis, cardiopulmonary complications. The acute phase physiotherapy program are positioning as the importance of early movement and mobilization to prevent pressure decubitus, passive and active exercises to treat contractures, breathing exercises to prevent pulmonary complications due to bed periods, and the main porpose is to educate patients and families about exercises before surgery is performed. Keyword: Spinal cord injury, acute, contracture, potitioning, mobilization